Bath's ironwork: wartime removal and its subsequent restoration. Issue 3 (2nd September 2019) - Forsyth, Michael
ABSTRACT: In 1942, three years into World War II, the Ministry of Supply ordered that all cast and wrought iron in the city of Bath be removed for war purposes. This included the railings around garden squares, which were generally thought elitist and old-fashioned anyway. Ironwork could be retained on grounds of architectural or historic merit but reprieval was rare, and much fine ironwork that disappeared, mainly gates and railings, was first recorded by Official War Artists. Since the 1970s much of Bath's missing ironwork has been restored and the rest has undergone campaigns of repair, notably at Queen Square, Royal Crescent, Lansdown Crescent and Royal Victoria Park. An ongoing project to reinstate overthrows and lighting on the Bathwick estate coordinates best conservation practice, bringing together several materials and technologies of the 1790s.